In Vitro Assessment of Antioxidant Effect of Begonia rex Putz. Leaf Extract on Oxidative Stress Biomarkers In The Equine Erythrocytes Model - Buyun, Lyudmyla; Tkachenko, Halyna; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The main goal of our study was to assess the antioxidant effect of leaf extract obtained from Begonia rex Putz. on oxidative stress biomarkers [2-thiobarbituric acid reactive substances (TBARS), carbonyl derivatives content of protein oxidative modification] and antioxidant defences [superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) activity, ceruloplasmin level, and total antioxidant capacity] using the equine erythrocytes model. Freshly collected B. rex leaves were washed, weighted, crushed, and homogenized in 0.1M phosphate buffer (pH 7.4) (in ratio 1:19, w/w) at room temperature. The extracts were then filtered and used for analysis. A volume of 0.1 ml of the plant extract was added to 1.9 ml of clean equine erythrocytes or 1.9 ml of plasma. For positive control (phosphate buffer) was used. After incubation, the mixture at 37°C for 60 min with continuous stirring, erythrocytes, and plasma aliquots was used in the study. The extract during incubation of erythrocyte suspension caused a non-considerable TBARS formation (by 18 %, p>0.05), while the content of aldehydic and ketonic derivatives of oxidatively modified proteins was decreased (by 7 and 8 %, p>0.05, respectively) compared to control. The aqueous leaf extract of B. rex has proven the most effective to increase the catalase and GPx activity (by 44 %, p>0.05 and 62 %, p<0.05). The increase of the catalase and GPx activity was induced by TAC enhancement by 34 % (p>0.05). SOD activity was non-significantly decreased by 17% (p>0.05). B. rex extract caused the statistically significant decrease in ceruloplasmin level by 64 % (p<0.05). These in vitro assays indicate that B. rex leaf extract screened is a significant source of natural antioxidant, which might be helpful in preventing the progress of various oxidative stresses. However, the components responsible for the antioxidative activity of B. rex extract is currently unclear. Therefore, further investigations need to be carried out to isolate and identify the antioxidant compounds present in the plant extract.